2012
DOI: 10.1017/orp.2012.4
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of Workplace Aggression: The Influences of Social Support and Training

Abstract: Reception and administrative employees may be particularly vulnerable to patient aggression in mental health services. This study examined whether satisfaction with social support and primary aggression training moderated the effects of perceived aggression on psychological distress and somatic symptoms in a sample of 101 employees. The biophysical model of threat and challenge, the stressor-stress-strain model, and the stress-buffering hypothesis served as theoretical frameworks. Results showed perceived aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
1
8
0
1
Order By: Relevance
“…The questionnaire was a victimization survey developed by the VISAGE research team and derived from the Perceptions of Prevalence of Aggression scale (POPAS; Oud, 2001), which is a reliable instrument (Cronbach’s alpha ranging between 0.70 and 0.91) to measure aggressive patient behaviors experienced by workers in the healthcare sector in the last 12 months (Brown, Loh, & Marsh, 2012; Gale et al, 2009; Nijman, Bowers, Oud, & Jansen, 2005). What distinguishes this tool from other instruments is that it measures workplace violence in an exhaustive manner by assessing different types of workplace violence experiences, not only the sum of all kinds of incidents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was a victimization survey developed by the VISAGE research team and derived from the Perceptions of Prevalence of Aggression scale (POPAS; Oud, 2001), which is a reliable instrument (Cronbach’s alpha ranging between 0.70 and 0.91) to measure aggressive patient behaviors experienced by workers in the healthcare sector in the last 12 months (Brown, Loh, & Marsh, 2012; Gale et al, 2009; Nijman, Bowers, Oud, & Jansen, 2005). What distinguishes this tool from other instruments is that it measures workplace violence in an exhaustive manner by assessing different types of workplace violence experiences, not only the sum of all kinds of incidents.…”
Section: Methodsmentioning
confidence: 99%
“…The literature on both healthcare and law enforcement sectors have also addressed the importance of support from colleagues and supervisors, which were found to buffer the effects of workplace violence (Brown et al, 2012;Littlechild, 2005). However, since habituation and acceptance of workplace violence are the results of professional socialization, support from colleagues and supervisors may positively relate to trivialization of violence (Brown et al, 1999;Dick, 2000).…”
Section: Organizational Factorsmentioning
confidence: 99%
“…Likewise, there is evidence of the protective effect of organisational support in situations of patient violence. Indeed, when employees find their work environment supportive, they are partially protected against the psychological consequences of patient violence (Brown, Loh, & Marsh, 2012; Magnavita, 2014; Zhao et al, 2015). For example, Mueller and Tschan (2011) found that social services employees who felt supported by their employer were more likely to cope well in the aftermath of a client assault.…”
Section: Identifying Job Resources For Coping With Patient Violencementioning
confidence: 99%
“…Les études qui l'ont utilisé ont obtenu des alphas de Cronbach allant de 0,70 à 0,90 (Brown, Loh, et Marsh, 2012;Gale et al, 2009;James et al, 2011;Jonker et al, 2008;Nijman et al, 2005). Selon George et Mallery (2003), ces coefficients indiquent une cohérence interne allant d'acceptable (a = 0.70) à excellente (a = 0.90).…”
Section: Le Popasunclassified